2016
DOI: 10.22192/ijamr.2016.03.11.008
|View full text |Cite
|
Sign up to set email alerts
|

OECD Principles of Corporate Governance: Compliance among Ghanaian Listed Companies.

Abstract: This study has explored the corporate governance practices in Ghanaian listed firms using the OECD five principles of corporate governance. These principles are: Rights of Shareholders, Equitable Treatment of Shareholders, Roles of Stakeholders in Corporate Governance, Disclosure and Transparency, and Responsibility of the Board. A set of questionnaire containing carefully selected questions on each principle was administered in 20 selected firms on the Ghana stock market. The participants included three stake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There is ongoing campaign for the need to entrench corporate governance as a control strategy and impetus towards attaining organization's goals. Studies have confirmed a structural shift in corporate governance and high level of compliance among firms in Nigeria (Akinkoye & Olasanmi, 2014;Gyamerah, & Agyei, 2016;Araniyar & Chizea, 2017;Aiwanehi, et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…There is ongoing campaign for the need to entrench corporate governance as a control strategy and impetus towards attaining organization's goals. Studies have confirmed a structural shift in corporate governance and high level of compliance among firms in Nigeria (Akinkoye & Olasanmi, 2014;Gyamerah, & Agyei, 2016;Araniyar & Chizea, 2017;Aiwanehi, et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…The concept of corporate governance now covers as well as the major issues of an organizations ranging from its ownership structure to the process and procedures of the firm (Gyamerah & Agyei, 2016).…”
Section: Corporate Governancementioning
confidence: 99%
“…There is no single model of good corporate governance, however, the principles proposed by Organization for Economic Co-Operation and Development (OECD 2004) for good corporate governance that is based on common elements and different models that already exist. Corporate governance is about what the board of a company does and how it sets the values of the company, and it is to be distinguished from the day-to-day operational management of the company by full-time executives (Gyamerah & Agyei, 2016). Thus, this system supports the financial and capital market of a country.…”
Section: Introductionmentioning
confidence: 99%